Запліднення, ендоспермо- та ембріогенез у Adonis vernalis L. (Ranunculaceae) - Марко, Н.В.; Шевченко, С.В. (Український ботанічний журнал, 2012)
Представлены результаты исследования отдельных этапов репродуктивного процесса редкого вида Adonis vernalis L., который имеет охранный статус. Установлены особенности оплодотворения, эндоспермогенеза и развития зародыша, приведены календарные сроки их протекания у данного вида в условиях Крыма. Работа иллюстрирована микрофотографиями. Results of the research on certain stages of reproductive process in a rare species, Adonis vernalis L., are presented. Some peculiarities of lobule fertilization, endosperm and embryo development are reported. Calendar terms for these processes in Crimea are provided. The article is illustrated by microphotographs.